Methylenetetrahydrofolate reductase gene A1298C polymorphism and susceptibility to recurrent pregnancy loss: a meta-analysis - Rai, V. (Cellular and Molecular Biology, 2014)
Environmental and genetic factors are thought to be involved in the pathogenesis of recurrent pregnancy loss (RPL)/spontaneous abortions (SA), which include endocrine, anatomical abnormalities within the genital organs, autoimmune diseases and some gene variants. Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme of the folate/methionine metabolic pathway and it is well established fact that folate deficiency causes pregnancy complications like recurrent pregnancy loss, preeclempsia and birth defects affected pregnancies. MTHFR A1298C polymorphism reduces the enzymatic activity and mimics as folate deficiency. To date, many studies have investigated the association between MTHFR A1298C polymorphism and RPL risk; however, the result is still controversial and inconclusive. The aim of the present study was to address the association of MTHFR A1298C polymorphism with RPL risk by meta-analysis. By searching electronic databases, total seventeen studies were identified for present meta-analysis. Crude odds ratios (OR) with 95 % confidence intervals (CIs) was used to assess the strength of association between A1298C polymorphism and RPL. The results indicate that the A1298C polymorphism is not associated with RPL (ORCvs A = 1.13 ,95 % CI= 0.87-1.46, P = 0.36 ; ORACvs AA = 1.22 ,95 % CI= 0.94- 1.6, P = 0.13; ORCCvsAA =1.35, 95 % CI= 76-2.36, P = 0.30; ORCC+AC vs AA = 1.15, 95 % CI= 88 -1.49, P = 0.29; ORCCvs AC+AA = 1.29, 95 % CI= 76 -2.12, P = 0.34). Further prospective studies were needed to confirm the precise relationship between the MTHFR A1298C polymorphism and RPL.